2012
DOI: 10.5539/ies.v5n3p56
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Networking Sites among Malaysian University Students

Abstract: Social networking sites (SNSs) have increasingly become an important tool for young adults to interact and socialize with their peers. As most of these young adults are also learners, educators have been looking for ways to understand the phenomena in order to harness its potential for use in education. This is especially relevant in Malaysia where SNSs are popular among the youths, yet there is little data available to describe patterns of use for the wider segment of the target population. This study present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 22 publications
12
58
0
Order By: Relevance
“…To conclude, the paper's findings came generally in line with previous empirical research underlining the growing tendency for students to use Facebook for academic purposes (e.g., Eteokleous et al, 2012;Hamat & Embi, 2012). The results also contradicted with some earlier research underlining less favorable attitudes towards Facebook application for academic purposes (e.g., Hrastinski & Aghaee, 2012;Haytko & Parker, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…To conclude, the paper's findings came generally in line with previous empirical research underlining the growing tendency for students to use Facebook for academic purposes (e.g., Eteokleous et al, 2012;Hamat & Embi, 2012). The results also contradicted with some earlier research underlining less favorable attitudes towards Facebook application for academic purposes (e.g., Hrastinski & Aghaee, 2012;Haytko & Parker, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…The study also showed that 49.7% of students use Facebook for educational purposes. A study conducted by Hamat, Embi, and Hassan (2012) in Malaysian context found that 84% of Malaysian students use social networking sites to interact and communicate with their peers for informal learning purpose. In the other side, only 49.7 of students communicate with their lecturers for academic matters.…”
Section: Facebook Use Among University Studentsmentioning
confidence: 99%
“…They found that students of Queensland University of Australia had deeper and longer learning and had the ability to be more innovative in their research assignment because of using Wiki-spaces (http://www.wikispaces.com) to do their assignments. Furthermore, [20] conducted a study to understand how Malaysian students' use SNSs; the study was on tertiary level included more than 6000 students. Their study confirmed that students are using SNSs for different purposes as it helps them to interact with their peers in order to engage in discussion and informal learning processes.…”
Section: Social Networking Sites As Educational Toolmentioning
confidence: 99%